2016
DOI: 10.1021/acs.chemmater.6b01360
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Gram-Scale Synthesis of Nitrogen and Sulfur Embedded Organic Dots with Distinctive Fluorescence Behaviors in Free and Aggregated States

Abstract: We report a new strategy for the gram-scale synthesis of highly blue fluorescent nitrogen and sulfur embedded organic dots through one-pot hydrothermal condensation of citric acid (CA) with cysteamine (Cys) at 200 °C. Under such circumstance, the dehydration between CA and Cys produces a molecular fluorophore, which self-assembles to amorphous dots through hydrophobic interaction and π–π stacking. In aqueous solution, the dots exhibit a very high fluorescent quantum yield that is above those of most photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 27 publications
6
83
0
Order By: Relevance
“…A remarkable change in color can be observed on some C-dots aggregating in solutions (see Section 3.2.) and, when comparing them in liquid and aggregated states [246], one can find its explanation. It can be suggested that the coherent exciton transfer operating within the particle is complemented by incoherent hopping on the particle aggregation.…”
Section: Coherent and Non-coherent Exciton Transfermentioning
confidence: 92%
“…A remarkable change in color can be observed on some C-dots aggregating in solutions (see Section 3.2.) and, when comparing them in liquid and aggregated states [246], one can find its explanation. It can be suggested that the coherent exciton transfer operating within the particle is complemented by incoherent hopping on the particle aggregation.…”
Section: Coherent and Non-coherent Exciton Transfermentioning
confidence: 92%
“…[16, 46, 57] Accordingly, many citrate-based CDs were synthesized using hydrothermal treatments. For instance, Dong et al prepared nitrogen and sulfur co-doped CDs (N,S-CDs) from CA and L-cysteine using a one-step hydrothermal treatment.…”
Section: Citrate-based Carbon Dots (Cds)mentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Lanthanide-doped CQDs can act as new probes with near infra-red fluorescence or fluorescence/magnetic resonance dual response. [30][31][32][33] However, the development of functional CQDs doped with transition metal using fixed metal complexes as precursors is yet to be reported.…”
mentioning
confidence: 99%